2020
DOI: 10.3390/s20154214
|View full text |Cite
|
Sign up to set email alerts
|

Vision System for Automatic On-Tree Kiwifruit Counting and Yield Estimation

Abstract: Yield estimation is an essential preharvest practice among most large-scale farming companies, since it enables the predetermination of essential logistics to be allocated (i.e., transportation means, supplies, labor force, among others). An overestimation may thus incur further costs, whereas an underestimation entails potential crop waste. More interestingly, an accurate yield estimation enables stakeholders to better place themselves in the market. Yet, computer-aided precision farming is set to play a pivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Preharvest fruit yield estimation (i.e., fruit yield is the amount of fruit product in Kg per −1 tree or Kg ha −1 ) is critical for strategic market planning for both small-scale farmers and large-scale farming companies. Therefore, the total yield was estimated by multiplying mean fruit weight by the total number of fruits per tree (fruit load) [33,34]. In addition, we calculated yield efficiency (kg m −3 ) by dividing the yield for an individual tree by its respective canopy volume.…”
Section: Yield Estimation and Yield Efficiencymentioning
confidence: 99%
“…Preharvest fruit yield estimation (i.e., fruit yield is the amount of fruit product in Kg per −1 tree or Kg ha −1 ) is critical for strategic market planning for both small-scale farmers and large-scale farming companies. Therefore, the total yield was estimated by multiplying mean fruit weight by the total number of fruits per tree (fruit load) [33,34]. In addition, we calculated yield efficiency (kg m −3 ) by dividing the yield for an individual tree by its respective canopy volume.…”
Section: Yield Estimation and Yield Efficiencymentioning
confidence: 99%
“…Work in precision agriculture has been conducted for several decades but has taken off more recently with significant advances in robotics and machine vision. Most of the automation work in this area has focused on harvesting [Silwal et al, 2017;Williams et al, 2019;Williams et al, 2020b], or pollination [Amador and Hu, 2017;Ohi et al, 2018;Williams et al, 2020a;Williams et al, 2021] tasks to supplement the workforce directly. However, yield estimation is a critical area for planning the overall workload throughout the season, and accurate crop yield measurements can provide key information for predicting workload throughout the year.…”
Section: Related Workmentioning
confidence: 99%
“…The experimental results showed that the tracking confidence was greatly enhanced after algorithm improvement. However, this method did not work for a long time and only performed counting for videos within 30 s. Mekhalfi et al (2020) proposed a counting method using LAB color space and Adaboost to determine the location of kiwi fruit. The disadvantages of this method were its inability to achieve real‐time operation and its poor robustness.…”
Section: Related Workmentioning
confidence: 99%